Compatibility of Cotton Confectionary Fat with Natural Cocoa Butter (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
The article deals with the methods of hydrogenation and perietherification, the opportunity of obtaining cocoa oil substitute, which is close to the natural cocoa oil in its physical and chemical dualities as its freezing and melting temperature, solidity, the content of triglycerids of fraction and etc. New scientific, experimental and practical results of obtaining cocoa oil substitute have been presented.